Students’ Perception of Digital Learning Resources in Enhancing Their Vocabulary-Building Skills - Nadira, Septiyana; Ningsih, Sri Kusuma (JET ADI BUANA, 2025)
Language education has evolved significantly with the rapid advancement of digital technology, providing students with more interactive and engaging resources for vocabulary building. However, despite the increasing availability of digital learning resources (DLRs), a gap remains in students' perceptions of how these tools support their vocabulary development—particularly among high school students. This study investigates high school students’ perceptions of DLRs in enhancing vocabulary-building skills. A quantitative method was employed, collecting data from 236 high school students in the JABODETABEK area via an online questionnaire adapted from a previous study. The instrument demonstrated high internal reliability (Cronbach’s Alpha = 0.907). Descriptive analysis revealed that over 70% of students agreed or strongly agreed that DLRs are effective, enjoyable, and beneficial for vocabulary learning. Simple linear regression analysis showed a strong and significant positive correlation (R = 0.730, R² = 0.533, p = 0.001) between students' perceptions and the enhancement of their vocabulary-building skills. These findings indicate that positive student perceptions significantly predict vocabulary development. By offering a flexible, media-rich, and self-directed learning experience, DLRs play a crucial role in enhancing vocabulary acquisition. To maximize student learning outcomes, the integration of DLRs into language instruction should be prioritized.